Spatial multicriteria decision analysis for Walking School Bus target development strategies. (September 2022) - Hayes, Alexander; Wang, Judith Y.T.; Nikitas, Alexandros
Abstract: Introduction: Around the world there has been a decline in the mode share of walking to school. This is the result of many factors influencing the mode choice decisions of parents for their own journeys to work and their children's journeys to school. Walking School Bus (WSB) has been proved to be an effective strategy that can be an innovation to promote walking to school and combat the 'vicious circle' of chauffeuring children to school. This modal switch can thus be a key for enhancing the sustainability of our transportation system and more importantly the health of our next generation. Methods: This paper proposes an innovative decision analysis model to identify areas for targeting WSB development. By applying spatial multicriteria decision analysis (SMCDA) to existing aggregate data on both work and school trip mode choices and relevant zonal characteristics, the proposed model can help planners and policy decision makers to identify where investments on setting up/enhancing WSBs might be most effective in enabling modal shift. We apply our SMCDA model to a case study in Bradford, UK. We highlight zones/schools within the study area where WSB programmes can be most effective to help realise the full potential of walking to school in health, environmental and social inclusion terms. Results: Six zones in Bradford have been identified as the areas with the highest potential for the uptake of WSB schemes. These present characteristics that are favourable conditions for walking but with less than ideal current walking mode shares. They have large numbers of school aged children, lower level of work trips by car and higher parents' availability. Conclusions: Our SMDCA method for WSB target development is highly transferable and can be applied to other cities in the UK or around the world; providing genuine applied value as an apparatus for supporting, informing and systematising the implementation of potentially successful (in engagement and usage terms) WSB schemes.